An Unusual Complication in Plastic Periodontal Surgery - Jorge Vagarinho; Sara Sardinha; Ricardo Alves (Case Reports in Dentistry)
Introduction. Oroantral communications may arise as a result of pathological processes or iatrogenic situations, particularly in oral surgery and implantology, but are uncommon in periodontal plastic surgery. Case Presentation. A healthy 37-year-old female patient with 5 mm Miller Class II recession on the maxillary left second molar was referred for a root coverage procedure. While preparing the recipient bed for the graft, an oroantral communication was created. Schneiderian membrane was sutured to reduce the dimension of the communication and covered with a connective tissue graft. Finally, the flap was laterally and coronally moved, and the patient instructed about postoperative precautions. This procedure allowed to achieve a complete closure of the oroantral communication and good root coverage after an 8-month follow-up. Conclusions. Different authors described different techniques that can be used to close oroantral communications. Nevertheless, in this clinical case, it was shown that the oroantral communication may be closed without having to postpone the periodontal plastic surgery.